Design and evaluation of solar power plant-based learning media for renewable energy education in high schools - Entang Entang; Beta Kurnia Illahi; Andreny Dwi Nurlita; Dadi Rusdiana (Journal of Counseling, Education and Society, 2024)
This research aims to develop renewable energy learning media in the form of a Solar Power Plant (PLTS), assess its feasibility, and analyze students' responses to the Renewable Energy Learning Media in the form of a Solar Power Plant (PLTS) in a high school in Bandung. This study is a type of developmental research that produces a product in the form of Renewable Energy Learning Media (Pane Surya). The research design adopts the Richey and Klein model with the stages of Design, Development, Implementation, and Decision Making. Data collection in this study was carried out using questionnaires. The results show that students' responses to the developed learning media indicate 80% for the attractiveness indicator, which falls under the high category; 81% for the usefulness indicator, categorized as high; and 79% for the ease-of-use indicator, also in the high category. Based on the research results, the renewable energy learning media in the form of a solar panel is deemed feasible to use and received positive responses from students during the renewable energy learning process in a high school in Bandung.